Novel Imido‐Cr/Silica Ethylene Polymerization Catalysts Modified from the Phillips Catalyst. Issue 6 (4th September 2022) - Jin, Yulong; Yang, Yang; Su, Changzhi; Wang, Junrong; Wang, Yongnian; Liu, Boping
Abstract: In this work, novel imido‐Cr/silica catalysts are synthesized by modifying the Phillips catalyst CrO x /silica with isocyanates. The imido‐Cr/silica, which has moderate activities of 200–300 kgPE molCr −1 bar −1, shows lower efficiency than CrO x /silica for C2 H4 polymerization. On the other hand, regarding to the modified catalysts, the productivity can be improved almost linearly with increasing C2 H4 pressure, and very stable activities are observed during the 1 h run of C2 H4 polymerization. When compared with CrO x /silica, the modified catalysts can produce polyethylene (PE) with much higher molecular weight (MW) and broader molecular weight distribution (MWD), which is featured by a distinct ultrahigh MW shoulder. Meanwhile, the MW and MWD of the PE products can be reduced obviously by adding a small amount of H2 before C2 H4 polymerization. In addition, it is found that more 1‐hexene can be copolymerized by CrO x /silica, and it is preferentially incorporated into a portion of the PE chains. While such a preference is much less significant for the modified catalysts. Abstract : Novel imido‐Cr/silica C2 H4 polymerization catalysts are synthesized by simply modifying the Phillips catalyst with isocyanates. The modified catalysts present lower activities and 1‐hexene incorporation ability, but show more stable activities and excellent H2 sensitivity, and their polyethylene products are featured by much higher molecular weight and broader molecular weight distribution.